ST-43AB : an optimal design tool for the design of continuous beam using microsoft excel - Teo, Zheng Liang (2014)
The project is a continuation from a previous final year project that involved the development of a spreadsheet using Microsoft Excel to design for steel beams up to Eurocode 3 standard. In this project, the purpose is to improve the efficiency of the current design tool by implementing a system which will optimize the selection of a steel beam to design continuous beam subjected to bending only. This report serves to document the development and improvement made to the Microsoft Excel Spreadsheet program. Microsoft Excel 2010 and Visual Basics for Application (VBA) is the foundation used to create this steel beam design program.